Treatment for Open Limb Compression Injury: Clinical and Experimental Study - V. N. Drobotov (Общая реаниматология, 2008)
Objective: to study the impact of local use of oxygenized perfluorane on the severity of reperfusion syndrome and local postis-chemic complications in open limb compression injury in an experiment, to develop a scheme for predicting its severity, and to test the local use of perfluorane, by taking into account the severity of the injury. Materials and methods. The experiments were carried out on 95 rats, including 40 rats as a study group, 40 animals as a control group, and 15 animals as an intact group. Severe open limb compression injury was inflicted on the study and control group animals under anesthesia. Oxygenized perfluorane was locally applied to the study group animals. The therapeutic effect of perfluorane was evaluated by the clinical picture, laboratory tests, tissue oxygen tension and the morphological changes in the afflicted tissues and vitals. The prediction of the severity of limb compression injury was based on the extent of injured soft tissues, the time of compression, age, and the pattern of a wound. By taking into account the predicted severity of open leg compression injury, its complex treatment involved oxygenized perfluorane locally used before primary surgical debridement and within further 5 days once daily. Results. The experimental model of open limb compression injury has provided evidence that the local use of oxygenized perfluorane diminishes the manifestations of endo-toxicosis and tissue hypoxia, preserves the vitality of afflicted tissues, and prevents infectious complications. A procedure has been developed to predict the severity of open limb compression injury. The local clinical application of perfluorane with the injury severity prediction being borne in mind could improve the outcomes of treatment. Conclusion. The results of the performed experiment and clinical trials show it expedient to locally use oxygenized perfluorane in non-life-threatening and life-threatening open limb compression injury. Key words: open limb compression injury, endotoxicosis, prognosis, perfluorane.